Fe3O4@SiO2@KIT-6 as an Efficient and Reusable Catalyst for the Synthesis of Novel Derivatives of 3,3'-((Aryl-1-phenyl-1H-pyrazol-4- yl)methylene)bis (1H-indole) - Nikpassand, Mohammad; Fekri, Leila Z.; Nabatzadeh, Mozhdeh (Combinatorial Chemistry & High Throughput Screening, 2017)
Aim and Objective: Korea advanced institute of science and technology cubic ordered mesoporous silica (KIT-6 mesoporous) silica coated magnetite nanoparticles, is an effective, ecobenign and recyclable catalyst for the electrophilic substitution reactions of indoles with various synthetized aldehydes to afford the corresponding novel diindolylmethanes in high yields and short reaction times. The catalyst can be recovered and reused without loss of activity. The work-up of the reaction consists of a simple separation, followed by concentration of the crude product and purification. The present methodology offers several advantages such as aqueous media, excellent yields, simple procedure, mild conditions and reduced environmental consequences. All of synthesized compounds are new and were characterized by IR, NMR and elemental analyses. Materials and Methods: A mixture of synthetized pyrazolecarbaldehydes [24] (2.0mmol), indole (4.0mmol) and Fe3O4@SiO2@KIT-6 (0.04mmol) and H2O (10mL) were stirred at room temperature for the required reaction time according to Table 2. After completion of the reaction, the product was solved in CHCl3 (30 mL) and insoluble catalyst was removed by filtration in the presence of an efficient magnetic bar. The organic phase including the product and CHCl3 was evaporated under vacuum. The resulting crude material was purified by recrystallization from EtOH to afford pure products. Results: As part of our on interest for the development of efficient and environmentally friendly procedures for the synthesis of heterocyclic and pharmaceutical compounds, an efficient, facile and aqueous media was introduced for the synthesis of novel derivatives of diindolylmethanes containing pyrazole moiety. A variety of synthetized aldehyde compounds reacted smoothly with indoles to produce diindolylmethanes under these reaction conditions. The electron deficiency and the nature of the substituents on the aromatic ring show some effects on this conversion. All the reactions were run with catalytic amounts of catalysts. The best results gained with 0.04mmol of Fe3O4@@SiO2@KIT-6 as a strong Lewis acid at room temperature in aqueous media. Conclusion: In conclusion, we have investigated the synthesized KIT-6 mesoporous silica coated magnetite nanoparticles (MMNPs) as a mild and efficient catalyst for the synthesis of novel diindolylmethanes coupled with pyrazole moiety in aqua media. The simplicity, easy workup together with the use of inexpensive, environmentally friendly and reusable catalyst, is the notable features of this catalytic procedure. To the best of our knowledge, this is the first report for the synthesis of a new library of diindolylmethane compound bearing pyrazole moiety that enhance the biological and pharmacological activity.
Keywords: Indole